1982
DOI: 10.1007/bf02553616
|View full text |Cite
|
Sign up to set email alerts
|

Prospective studies on the etiology and treatment of pruritus ani

Abstract: Seventy-five patients presented with the complaint of pruritus ani. The following prospective studies were employed to evaluate groups of these patients; (1) laboratory, including blood count, stool examination for ova and parasites, urinalysis, Sequential Multiple Analysis-12 serum studies, stool pH, and skin scrapings for fungi; (2) Minnesota Multiphasic Personality Inventory; (3) anal manometry; (4) elimination of dietary factors, and (5) topical ointment application. Many patients were concerned that a can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
9

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 6 publications
0
56
1
9
Order By: Relevance
“…These results partially contradict those of Smith et al [11], who administered the MMPI to 25 pruritus ani patients and found no statistically significant deviations on the clinical scales but a relatively high degree of inhibition and denial of feelings of social and emotional alienation. The high rate of psychological disorders in patients with pruritus ani found in our study confirms the clinical impressions of many authors [1,5,6], In his study, Laihinen [12] showed that psychiatric disturbance was clearly more common in itching dermatoses than in the general popu lation.…”
Section: Discussioncontrasting
confidence: 57%
“…These results partially contradict those of Smith et al [11], who administered the MMPI to 25 pruritus ani patients and found no statistically significant deviations on the clinical scales but a relatively high degree of inhibition and denial of feelings of social and emotional alienation. The high rate of psychological disorders in patients with pruritus ani found in our study confirms the clinical impressions of many authors [1,5,6], In his study, Laihinen [12] showed that psychiatric disturbance was clearly more common in itching dermatoses than in the general popu lation.…”
Section: Discussioncontrasting
confidence: 57%
“…In de literatuur worden psoriasis [Smith 1982], hemorroïden en contactallergie [Weichert 2004, Gopal 2002, Dasan 1999] als oorzaak van pruritus ani beschreven, net als bacteriële (streptokokken)infectie [Sheth 2007, Giordano 1999, hivgerelateerde infecties, erythrasma [Smith 1982], eczeem, lichen sclerosus [Zuccati 2005, Heard 2004, Weichert 2004, Gopal 2002, Harrington 1992, ziekte van Paget [Khoubehi 2001, Shutze 1990], fl uor vaginalis en seksueel overdraagbare aandoeningen [Zuccati 2005]. Proctologische aandoeningen die met anale jeuk gepaard kunnen gaan zijn fi ssura ani, fi stels en ziekte van Crohn.…”
Section: Nootunclassified
“…Regelmatig treedt jeuk op door locale irritatie door feces (diarree) [Farage 2007], urine-incontinentie, zeep en (vochtig) toiletpapier (met name het conserveermiddel kan klachten geven) [Zuccati 2005, Weichert 2004]. Abnormale relaxatie van de interne anale sfi ncter kan door lekkage van vocht en/of feces jeuk veroorzaken [Zuccati 2005, Heard 2004, Wigersma 1997, Smith 1982. Soms wordt vermeld dat psychische factoren een rol kunnen spelen [Zuccati 2005, Heard 2004, Wigersma 1997], maar daarvoor is geen bewijs gevonden.…”
Section: Nootunclassified
See 2 more Smart Citations